1994
DOI: 10.1557/jmr.1994.0781
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the assembly conditions of dielectric particles in uncured thermoset polymers

Abstract: It has been found that electric field induced fibrolysis of suspended dielectric powder in a variety of uncured thermoset polymeric materials is a potential fabrication means to assemble ceramic-polymer composites. The resulting composite material consists of a quasi 1–3 connectivity pattern due to the formation of fibrils by the ceramic powder. For a given thermoset polymer, the degree to which these fibrils form is strongly dependent on both the magnitude and frequency of the applied field. Fibril formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…2,3 Several potential applications have been proposed, such as temperature sensors, 4 dielectrics for embedded capacitors, 3,5 and piezoelectric elements for energy harvesting. 6 It has been shown recently that the alignment of PZT equiaxed granulate particles in an epoxy resin results in an improvement of the piezoelectric properties over 0-3 composites with randomly dispersed particles.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several potential applications have been proposed, such as temperature sensors, 4 dielectrics for embedded capacitors, 3,5 and piezoelectric elements for energy harvesting. 6 It has been shown recently that the alignment of PZT equiaxed granulate particles in an epoxy resin results in an improvement of the piezoelectric properties over 0-3 composites with randomly dispersed particles.…”
Section: Introductionmentioning
confidence: 99%
“…14 The dielectrophoretic effect can be utilized to manipulate particles dispersed in a fluid medium [15][16][17][18] and offers a simple alternative approach to create oriented particle filled polymer composites with anisotropic properties. [19][20][21][22][23][24] When an electric field is applied to an uncured thermosetting polymer, the dispersed particles form chains, which are fixed in place when the matrix is cured. Several studies reporting an increase in the permittivity of a composite material in the direction of these chains have been published, [25][26][27][28][29] However, the effect of the dielectrophoretic alignment on the piezoelectric properties, such as d 33 and g 33 , of piezoelectric particle-polymer matrix composites has not been explored yet, with the exception of one preliminary study.…”
Section: Introductionmentioning
confidence: 99%
“…Electric fields have also been used to make oriented structures in other polymer systems including one- 10,11 and two-phase 12,13 polymer solutions, block copolymer melts, [14][15][16][17] homopolymer/block copolymer mixtures, 18 and polymer/ceramic composites. 19,20 Morphology development in polymer mixtures containing two immiscible homopolymers dissolved in a mutual solvent in the presence of a dc electric field during solvent evaporation was first investigated by Venugopal et al [3][4][5] The polymer mixtures used included polystyrene (PS) with such other polymers as poly(ethylene oxide) (PEO), poly(methyl methacrylate) (PMMA), poly(vinyl acetate) (PVA), polybutadiene (PB), and poly(vinyl chloride) (PVC) in toluene or cyclohexanone as a solvent. They showed that when the dielectric constants of the dispersed phase ( d ) and the matrix ( m ) were about the same, namely, in the PS/ PB/toluene system, there was no apparent droplet deformation.…”
Section: Introductionmentioning
confidence: 99%